Tuberculous pleurisy mimicking Mycoplasma pneumoniae infection in a previously healthy young adult: A case report. Issue 20 (May 2018) - Yaguchi, Daizo; Ichikawa, Motoshi; Shizu, Masato; Inoue, Noriko; Kobayashi, Daisuke; Imai, Naoyuki; Ito, Masao
Abstract: Ratonale: Sometimes, pleural effusion accompanying an acute Mycoplasma pneumoniae infection or tuberculous pleurisy has similar analysis results. We report a case of tuberculous pleurisy which was initially diagnosed as acute M pneumoniae infection, which is of special interest because anti-Mycoplasma antibody results were positive, which served as a red herring. Patient concerns: A 20-year-old woman visited the outpatient emergency romm of our hospital for chief complaints of high fever, dry cough, and pleuralgia persiting for 2 days. Since anti-mycoplasma antibody test results were positive, we treated acute M pneumoniae infection and drained her pleural effusion. The condition tended to improve, but on day 16 postadmission, the acid-fast bacterial culture of the pleural effusion was positive for Mycobacterium tuberculosis . Diagnoses: Tuberculous pleurisy. Interventions: After the diagnosis, the patient received antituberculous drugs. Outcomes: She completed treatment with no noticeable adverse events, and the right pleural effusion disappered and diffuse right pleural thickening improved. Lessons: Exudative pleural effusion with lymphocyte dominance and a high adenosine deaminase level in M pneumoniae infection have been reported. Even though the condition suggests acute M pneumoniae infection, clinicians should be aware that tuberculous pleurisy and M pneumoniae infection can share similar clinical features, and should understand the usefulness and limitations of the anit-Mycoplasma antibody test.